2008
DOI: 10.5194/bg-5-1625-2008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing seasonality of biochemical CO<sub>2</sub> exchange model parameters from micrometeorological flux observations at boreal coniferous forest

Abstract: Abstract. The seasonality of the NEE of the northern boreal coniferous forests was investigated by means of inversion modelling using eddy covariance data. Eddy covariance data was used to optimize the biochemical model parameters. Our study sites consisted of three Scots pine (l. Pinus sylvestris) forests and one Norway spruce (l. Picea abies) forest that were located in Finland and Sweden. We obtained temperature and seasonal dependence for the biochemical model parameters: the maximum rate of carboxylation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 81 publications
(93 reference statements)
1
27
0
Order By: Relevance
“…The photosynthesis module in JSBACH has the same temperature response for parameters describing the potential electron transport rate and maximum carboxylation rate for the whole year, thus indicating that the simulated vegetation is ready to immediately photosynthesize in spring with increasing air temperatures without any recovery period required, providing there is foliage present as in the case of ENF. However, the boreal coniferous forests have a recovery period in spring after the winter dormancy before they reach their full summertime photosynthetic capacity [89,90]. This may explain the differences between observed GPP at Sodankylä and simulated GPP using local weather observations (Figures 4 and 5).…”
Section: Modelling Of Springtime Development and The Start Of Season mentioning
confidence: 78%
“…The photosynthesis module in JSBACH has the same temperature response for parameters describing the potential electron transport rate and maximum carboxylation rate for the whole year, thus indicating that the simulated vegetation is ready to immediately photosynthesize in spring with increasing air temperatures without any recovery period required, providing there is foliage present as in the case of ENF. However, the boreal coniferous forests have a recovery period in spring after the winter dormancy before they reach their full summertime photosynthetic capacity [89,90]. This may explain the differences between observed GPP at Sodankylä and simulated GPP using local weather observations (Figures 4 and 5).…”
Section: Modelling Of Springtime Development and The Start Of Season mentioning
confidence: 78%
“…Kuppel et al, 2014). Medvigy et al (2009) and Verbeeck et al (2011) both showed that parameters derived at one site can perform well on a similar site and over the surrounding region (Medvigy and Moorcroft, 2011). However, a contradictory study by Groenendijk et al (2010) found that there was cross-site parameter variability after optimisation within the PFT groupings.…”
Section: Introductionmentioning
confidence: 98%
“…of defining a model adjoint and minimising the error in the fit to data), are very similar in these two applications of data assimilation. This paper is certainly not the first to define parameter estimation of this form as data assimilation (Braswell et al, 2005;Stöckli et al, 2008;Verbeeck et al, 2011;Kuppel et al, 2012;Hararuk et al, 2014), but the reader should note the subtle difference between our definition of data assimilation and that commonly used in weather forecasting. Even a relatively simplistic land-surface representation such as JULES has over a hundred internal parameters representing the environmental sensitivities of the various land-surface types and PFTs within the model.…”
Section: Data Assimilation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…As observation sites have their own characteristics, it is necessary to make local site simulations for model evaluation and calibration as they may reveal new insight into model behaviour and guide further development. Model-data fusion has been applied for boreal forest sites by, e.g., Aalto et al (2004) Peltoniemi et al (2015b), Thum et al (2007Thum et al ( , 2008 and Wu et al (2011).…”
Section: Introductionmentioning
confidence: 99%